The Roles of Aesthetic and Cultural Perception Affected by Window Display of Thai Crafts Products to Increase Purchasing Intention - Kanokwan Somoon; Chumporn Moorapun (My University, 2016)
Window display of retail shops plays a significant role in attracting customers to visit and even to purchase products from the store. Therefore, the study aims to examine what kinds of perception influenced by a window display of Thai craft products and, in turns, affect purchasing intention. To investigate this relationship, 150 tourists around the world were recruited by using voluntarily online-survey. A set of perception was applied by using multiple regressions to examine the relationship between the perception and purchasing intention. The results found that only aesthetic and Thai unique culture are two significant factors that influence purchasing intention.
Keywords: Consumer Retail Behavior Studies